Seed fat from Madhuca longifolia as raw material for Halal alternative fats - Marikkar, Mohammed Nazrim (2012)

(untitled)
Lard extracted from swine is prohibited under halal and kosher food regulations. A study was carried out on Madhuca longifolia seed fat and lard to compare their solidification and melting characteristics to formulate halal alternative lipid substitutes. Initially, a direct comparison of lard with Madhuca longifolia seed fat was done with respect to thermal properties using differential scanning calorimetry (DSC) and pulse NMR spectroscopy. By subjecting these two fats to fractional crystallization under control temperature conditions in acetone, solid and liquid components of them were isolated individually. The thermal properties of the solid and liquid components from lard were also compared to those of lipid derivatives from Madhuca longifolia seed fat using DSC and NMR techniques. As the analytical data obtained from DSC and pulse NMR techniques showed that these two fats and their components were compatible in terms of their thermal properties, Madhuca longifolia seed fat could be a useful raw material for formulation of halal alternative fats.